Targeting the p53-MDM2 pathway for neuroblastoma therapy: Rays of hope - Zafar, Atif; Wang, Wei; Liu, Gang; Xian, Wa; McKeon, Frank; Zhou, Jia; Zhang, Ruiwen (Cancer letters, 2021)
Despite being the subject of extensive research and clinical trials, neuroblastoma remains a major therapeutic challenge in pediatric oncology. The p53 protein is a central safeguard that protects cells against genome instability and malignant transformation. Mutated TP53 (the gene encoding p53) is implicated in many human cancers, but the majority of neuroblastomas have wild type p53 with intact transcriptional function. In fact, the TP53 mutation rate does not exceed 1–2% in neuroblastomas. However, overexpression of the murine double minute 2 (MDM2) gene in neuroblastoma is relatively common, and leads to inhibition of p53. It is also associated with other non-canonical p53-independent functions, including drug resistance and increased translation of MYCN and VEGF mRNA. The p53-MDM2 pathway in neuroblastoma is also modulated at several different molecular levels, including via interactions with other proteins (MYCN, p14ARF). In addition, the overexpression of MDM2 in tumors is linked to a poorer prognosis for cancer patients. Thus, restoring p53 function by inhibiting its interaction with MDM2 is a potential therapeutic strategy for neuroblastoma. A number of p53-MDM2 antagonists have been designed and studied for this purpose. This review summarizes the current understanding of p53 biology and the p53-dependent and -independent oncogenic functions of MDM2 in neuroblastoma, and also the regulation of the p53-MDM2 axis in neuroblastoma. This review also highlights the use of MDM2 as a molecular target for the disease, and describes the MDM2 inhibitors currently being investigated in preclinical and clinical studies. We also briefly explain the various strategies that have been used and future directions to take in the development of effective MDM2 inhibitors for neuroblastoma. •Targeting p53-MDM2 Pathway is a validated approach for neuroblastoma Therapy.•MDM2 overexpression and constitutive activation are common in neuroblastoma.•MDM2 promotes chemical-induced carcinogenesis.•MDM2 promotes cancer progression by regulating multiple cellular functions; and.•MDM2 inhibitors have anticancer activity in neuroblastoma models.